Effects of Cyclosporine 0.05% ophthalmic solution on diagnostic parameters of dry eye disease - Sethi, Maneesha; Bali, Amarjeet Singh; Sadhotra, P. (International Journal of Research in Medical Sciences, 2017)
Background: Dry eye is a multifactorial disease particularly prevalent in Asia for which there are several treatments. Among anti-inflammatory treatment, cyclosporine 0.05% is preferred therapy. Our study evaluated effects of cyclosporine 0.05% ophthalmic solution on the diagnostic tools of dry eye. Material & Methods: A prospective study was carried out in ophthalmological outpatient department of ASCOMS and Hospital. Total 60 patients of dry eye disease who fulfilled the inclusion criteria were treated with cyclosporine 0.05% ophthalmic solution twice a day. The diagnostic parameters of dry eye were assessed at baseline, at month 1 and 3. Patients underwent Ocular Surface Disease Index (OSDI) score, Schirmer’s test, Tear film break up time (TBUT) . Results: After three months, mean OSDI score was significantly improved (p < 0.001). There was significant improvement in mean Schirmer score (p < 0.001). Baseline TBUT also increased significantly (p < 0.001). Conclusion: Cyclosporine 0.05% ophthalmic solution has significant effect on diagnostic parameters of dry eye disease.